Pengaruh Earning Per Share dan Current Ratio Terhadap Harga Saham Sektor Tambang Batu Bara di Bursa Efek Indonesia Tahun 2018-2022 - Isah Amini Yasmin; Kosasih (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The coal sector in Indonesia during 2018-2022 faced various challenges that had an impact on financial instability in companies, consequently affecting stock price fluctuations. The Covid-19 pandemic during 2019-2020 exacerbated the condition by causing a decline in stock prices. The principal objective of this study was to examine EPS and Current Ratio that influence stock price fluctuations in the coal mining sector on the IDX over that period. The quantitative method was selected as the research method, with data analysis conducted using the SPSS 27 software. In partial results demonstrated that both EPS and CR exert a positive influence on the stock prices. Furthermore, the simultaneous results indicated that EPS and CR also exert a significant simultaneous influence on the stock prices of coal mining sub-sector companies in IDX period 2018 to 2022.